A method for manufacturing an ultra-thin graphite bipolar plate for a fuel cell
The method addresses the challenges of bipolar plate brittleness and porosity in graphite plates by treating carbon fiber and expanded graphite, forming a conductive network with graphene and Ti3SiC2, achieving improved mechanical and electrical properties in ultra-thin graphite bipolar plates for fuel cells.
Patent Information
- Application Number
- CN202411208992.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-30
AI Technical Summary
Bipolar plates in fuel cells face challenges with corrosion resistance, brittleness, and processing difficulties, particularly in graphite plates, which affect their thickness and performance due to porosity issues.
A manufacturing method involving pre-treating carbon fiber and expanded graphite, forming a skeleton layer with carbon fiber cloth, and impregnating it with a conductive mixture of graphene, modified expanded graphite, and ceramic Ti3SiC2 nanopowder to enhance mechanical and electrical properties, using freeze-drying and hot pressing to achieve an ultra-thin graphite bipolar plate.
The method improves mechanical strength, bending resistance, and electrical conductivity while reducing porosity and gas permeability, resulting in a bipolar plate with enhanced performance and reduced thickness.
Abstract
Description
Technical Field
[0001] The invention relates to the field of fuel cells, and in particular to a method for manufacturing an ultra-thin graphite bipolar plate. Background Art
[0002] Bipolar plates, also known as current collectors, separate oxidants from reductants and distribute reactants evenly to the electrodes through the flow field on the plate surface to react electrochemically with the electrode catalyst layer. The basic requirements for bipolar plates are corrosion resistance, good conductivity, low air permeability, and light weight.
[0003] At present, the research and application of bipolar plates are mainly concentrated on metal plates and graphite plates. Metal bipolar plates have good strength, good conductivity, and good impermeability, but their weakness is poor corrosion resistance. Graphite plates have good conductivity, thermal conductivity, and corrosion resistance, but the brittleness of graphite makes processing difficult, so the processing cost is high, and it also limits the reduction of graphite plate thickness. In addition, graphite is prone to pores during the manufacturing process, which allows the fuel and oxidant to penetrate each other, affecting battery performance. Summary of the invention
[0004] The invention discloses a method for manufacturing an ultra-thin graphite bipolar plate for a fuel cell. The method comprises: pre-treating carbon fiber and expanded graphite, preparing fiber cloth from the pre-treated carbon fiber and using the fiber cloth as a skeleton layer of the bipolar plate, then forming a surface layer including the pre-treated expanded graphite on both sides of the skeleton layer, freeze-drying, hot pressing and curing to obtain a plate blank, impregnating the plate blank in an impregnating agent, heating and drying and curing to obtain an ultra-thin graphite bipolar plate for a fuel cell. The manufacturing method of the invention improves the mechanical strength and bending resistance of the bipolar plate, and can obtain a fuel cell bipolar plate with ultra-thin thickness, high conductivity, good mechanical properties and good air tightness.
[0005] Specific solutions include:
[0006] A method for manufacturing an ultra-thin graphite bipolar plate for a fuel cell, characterized in that it comprises the following steps:
[0007] 1) dispersing chloromethylated phenolic resin in N,N-dimethylformamide, adding sodium azide, reacting, and obtaining azidophenolic resin; immersing carbon fiber in hydrogen peroxide, heating in a sealed state, taking out and drying, and then placing in N-methylpyrrolidone containing azidophenolic resin, heating in a sealed state, taking out and drying, and obtaining pretreated carbon fiber; making a plurality of the pretreated carbon fibers into roving and weaving them into carbon fiber cloth;
[0008] 2) Weighing graphene and expanded graphite and mixing them by ball milling; then soaking them in a stannous nitrate solution, then soaking them in sodium hydroxide, and then soaking them in hydrogen peroxide to obtain expanded graphite modified with tin oxide and graphene; dispersing the modified expanded graphite and phenolic resin in N-methylpyrrolidone to obtain a mixed slurry;
[0009] 3) The mixed slurry is evenly coated on the carbon fiber cloth, freeze-dried, and then hot-pressed to obtain a plate blank;
[0010] 4) epoxy acrylate, methyl methacrylate and trimethylolpropane triacrylate are mixed evenly, and then ceramic Ti3SiC2 nano powder and silane coupling agent are added thereto, stirred evenly, and a peroxide initiator is added to obtain an impregnation solution;
[0011] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, and repeat vacuuming and pressurizing to make it fully impregnated;
[0012] 6) The impregnated expanded graphite sheet is heated and cured in a water bath, and then placed in an oven for drying and curing to obtain an ultra-thin graphite bipolar plate.
[0013] Furthermore, in the step 1, 18-20 g of chloromethylated phenolic resin is dispersed in 450-500 ml of N,N-dimethylformamide, 0.5-0.6 g of sodium azide is added, the reaction is completed at 40-50 ° C, and the mixture is washed with water to obtain an azid phenolic resin; 8-10 g of carbon fiber is immersed in hydrogen peroxide with a concentration of 4-6 wt%, heated at 80-100 ° C for 1-2 h, taken out and dried, and then placed in N-methylpyrrolidone containing 0.4-0.5 wt% of azid phenolic resin, heated at 150-180 ° C for 2-4 h, taken out and dried to obtain pretreated carbon fiber.
[0014] Furthermore, in the step 2, 2-4 g of graphene and 40-50 g of expanded graphite are weighed and ball-milled; then placed in a stannous nitrate solution with a concentration of 2-3 wt%, soaked for a predetermined time, filtered, the filtered solid is placed in sodium hydroxide and soaked for 0.5-1 h, filtered, the filtered solid is placed in hydrogen peroxide and soaked for 0.5-1 h, filtered, washed, and dried to obtain modified expanded graphite; 75-80 g of modified expanded graphite and 20-25 g of phenolic resin are dispersed in 200-250 ml of N-methylpyrrolidone to obtain a mixed slurry.
[0015] Furthermore, the parameters of the hot pressing curing in step 3 are as follows: the hot pressing temperature is 160-180° C., the pressure is 15-25 MPa, and the hot pressing time is 10-30 min; and a polar plate blank is obtained.
[0016] Furthermore, in step 4, 120-150 g of epoxy acrylate, 200-220 g of methyl methacrylate, and 60-80 g of trimethylolpropane triacrylate are mixed evenly, and then 20-25 g of ceramic Ti3SiC2 nanopowder and 5-10 g of silane coupling agent are added thereto, stirred evenly, and 5-10 g of benzoyl peroxide is added and stirred evenly to obtain an impregnation solution.
[0017] Furthermore, in step 5, the electrode plate is transferred to a sealed container, and the impregnation liquid is injected to immerse the electrode plate embryo in the impregnation liquid. The vacuum is evacuated to below 100Pa and maintained for 20-30 minutes. Then, the pressure is increased to 3-5MPa and maintained for 20-30 minutes. The vacuum and pressurization are repeated 3-5 times to ensure that the electrode plate embryo is fully impregnated.
[0018] Furthermore, in step 6, the temperature of the water bath is 80-90° C. for 4-5 hours, and then the plate is placed in an oven for drying and curing at a temperature of 150-170° C. for 1-2 hours to obtain an ultra-thin graphite bipolar plate.
[0019] An ultra-thin graphite bipolar plate for a fuel cell, the bipolar plate is prepared by the manufacturing method.
[0020] Beneficial technical effects of the present invention
[0021] 1) The present invention uses phenolic resin grafted carbon fiber woven into fiber cloth as the bipolar plate skeleton. Phenolic polyester can improve the mechanical strength and bending performance of carbon fiber. At the same time, the bonding degree between the grafted material and the expanded graphite slurry is greatly improved, thereby improving the mechanical properties of the bipolar plate. At the same time, the grafted carbon fiber cloth has excellent bonding performance with the expanded graphite layer, thereby improving the bending resistance of the graphite bipolar plate and the bonding strength between the skeleton layer and the surface layer.
[0022] 2) The present invention uses a mixture of expanded graphite and graphene. Graphene has good electrical conductivity. After modifying the expanded graphite, the electrical conductivity of the expanded graphite can be greatly improved. At the same time, tin oxide is further used for surface modification to improve the affinity with the phenolic resin, so that the graphene and expanded graphite can be evenly dispersed in the slurry to form a conductive network, thereby improving the electrical conductivity;
[0023] 3) Ceramic Ti3SiC2 nanopowder is a MAX phase ceramic material with high conductivity. The present invention uses titanium silicon carbide as a filling conductive medium. By adding it to the impregnation solution, it is dispersed into the pores of the bipolar plate during the impregnation process, thereby improving the conductivity and further improving the mechanical properties of the plate.
[0024] 4) The freeze-drying method of the present invention can form a porous graphite plate embryo, which is beneficial to the penetration of the impregnation liquid. At the same time, after the three acrylate monomers are compounded, they have a lower viscosity and good wettability with the plate embryo, which is beneficial to reducing the porosity of the plate and reducing the gas permeability. At the same time, the silane coupling agent is added to make the MAX phase of titanium silicon carbide uniformly dispersed in the pores of the plate, thereby improving the conductivity. DETAILED DESCRIPTION
[0025] The present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples within the scope not exceeding the gist of the present invention.
[0026] Example 1
[0027] 1) Disperse 18g of chloromethylated phenolic resin in 450ml of N,N-dimethylformamide, add 0.5g of sodium azide, react completely at 40°C, wash with water, and obtain azidophenolic resin; immerse 8g of carbon fiber in 4wt% hydrogen peroxide, heat at 80°C for 2h, take out and dry, then put into N-methylpyrrolidone containing 0.4wt% azidophenolic resin, heat at 150°C for 4h, take out and dry, and obtain pretreated carbon fiber; make a plurality of the pretreated carbon fibers into roving and then weave into carbon fiber cloth, wherein the linear density of the roving is 2000tex, and the gram weight of the fiber cloth is 600g•m -2 ;
[0028] 2) Weighing 2g of graphene and 40g of expanded graphite and mixing them by ball milling, wherein the ball milling speed is 1800r / min and the ball milling time is 4h; then placing them in a 2wt% stannous nitrate solution, soaking them for a predetermined time, filtering, soaking the filtered solid in sodium hydroxide for 1h, filtering, soaking the filtered solid in hydrogen peroxide for 1h, filtering, washing, and drying to obtain modified expanded graphite; dispersing 75g of modified expanded graphite and 20g of phenolic resin in 200ml of N-methylpyrrolidone to obtain a mixed slurry;
[0029] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 160°C, a pressure of 20 MPa, and a hot pressing time of 30 min to obtain a plate blank;
[0030] 4) 120 g of epoxy acrylate, 200 g of methyl methacrylate, and 60 g of trimethylolpropane triacrylate were mixed evenly, and then 20 g of ceramic Ti3SiC2 nanopowder and 5 g of silane coupling agent were added thereto, and stirred evenly, and 5 g of benzoyl peroxide was added, and stirred evenly to obtain an impregnation solution;
[0031] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 20 minutes, then pressurize to 3Mpa, maintain for 20 minutes, repeat the evacuation and pressurization 5 times to make it fully impregnated;
[0032] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 80°C for 4 hours, and then placed in an oven for drying and curing at 150°C for 1 hour to obtain an ultra-thin graphite bipolar plate.
[0033] Example 2
[0034] 1) Disperse 19g of chloromethylated phenolic resin in 460ml of N,N-dimethylformamide, add 0.55g of sodium azide, react completely at 45°C, wash with water, and obtain azidophenolic resin; immerse 9g of carbon fiber in 5wt% hydrogen peroxide, heat at 90°C for 1h, take out and dry, then put into N-methylpyrrolidone containing 0.5wt% azidophenolic resin, heat at 160°C for 3h, take out and dry, and obtain pretreated carbon fiber; make a plurality of the pretreated carbon fibers into roving and then weave into carbon fiber cloth, wherein the linear density of the roving is 2000tex, and the gram weight of the fiber cloth is 600g•m -2 ;
[0035] 2) Weigh 3g of graphene and 45g of expanded graphite and mix them by ball milling, wherein the ball milling speed is 1900r / min and the ball milling time is 3h; then place them in a 3wt% stannous nitrate solution, soak for a predetermined time, filter, soak the filtered solid in sodium hydroxide for 0.5h, filter, soak the filtered solid in hydrogen peroxide for 1h, filter, wash, and dry to obtain modified expanded graphite; disperse 76g of modified expanded graphite and 22g of phenolic resin in 220ml of N-methylpyrrolidone to obtain a mixed slurry;
[0036] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 170°C, a pressure of 20 MPa, and a hot pressing time of 20 min to obtain a plate blank;
[0037] 4) 130 g of epoxy acrylate, 210 g of methyl methacrylate, and 70 g of trimethylolpropane triacrylate were mixed evenly, and then 22 g of ceramic Ti3SiC2 nanopowder and 6 g of silane coupling agent were added thereto, and stirred evenly, and 6 g of benzoyl peroxide was added, and stirred evenly to obtain an impregnation solution;
[0038] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 25 minutes, then pressurize to 4Mpa, maintain for 25 minutes, repeat the evacuation and pressurization 4 times to make it fully impregnated;
[0039] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 80°C for 4 hours, and then placed in an oven for drying and curing at 160°C for 2 hours to obtain an ultra-thin graphite bipolar plate.
[0040] Example 3
[0041] 1) Disperse 20g of chloromethylated phenolic resin in 500ml of N,N-dimethylformamide, add 0.6g of sodium azide, react completely at 50°C, wash with water, and obtain azidophenolic resin; immerse 10g of carbon fiber in 6wt% hydrogen peroxide, heat at 100°C for 2h, take out and dry, then put into N-methylpyrrolidone containing 0.5wt% azidophenolic resin, heat at 180°C for 4h, take out and dry, and obtain pretreated carbon fiber; make a plurality of the pretreated carbon fibers into roving and then weave into carbon fiber cloth, wherein the linear density of the roving is 2000tex, and the gram weight of the fiber cloth is 600g•m -2 ;
[0042] 2) Weighing 4g of graphene and 50g of expanded graphite, mixing by ball milling, wherein the ball milling speed is 2000r / min, and the ball milling time is 4h; then placing in a 3wt% stannous nitrate solution, soaking for a predetermined time, filtering, soaking the filtered solid in sodium hydroxide for 1h, filtering, soaking the filtered solid in hydrogen peroxide for 1h, filtering, washing, and drying to obtain modified expanded graphite; dispersing 80g of modified expanded graphite and 25g of phenolic resin in 250ml of N-methylpyrrolidone to obtain a mixed slurry;
[0043] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 180°C, a pressure of 20 MPa, and a hot pressing time of 30 min to obtain a plate blank;
[0044] 4) 150 g of epoxy acrylate, 220 g of methyl methacrylate, and 80 g of trimethylolpropane triacrylate were mixed evenly, and then 25 g of ceramic Ti3SiC2 nanopowder and 10 g of silane coupling agent were added thereto, and stirred evenly, and 10 g of benzoyl peroxide was added, and stirred evenly to obtain an impregnation solution;
[0045] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 30 minutes, then pressurize to 5Mpa, maintain for 30 minutes, repeat the evacuation and pressurization 5 times to make it fully impregnated;
[0046] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 90°C for 5 hours, and then placed in an oven for drying and curing at 170°C for 2 hours to obtain an ultra-thin graphite bipolar plate.
[0047] Example 4
[0048] 1) Disperse 18g of chloromethylated phenolic resin in 500ml of N,N-dimethylformamide, add 0.6g of sodium azide, react completely at 40°C, wash with water, and obtain azidophenolic resin; immerse 10g of carbon fiber in 4wt% hydrogen peroxide, heat at 80°C for 2h, take out and dry, then put into N-methylpyrrolidone containing 0.5wt% azidophenolic resin, heat at 180°C for 2h, take out and dry, and obtain pretreated carbon fiber; make a plurality of the pretreated carbon fibers into roving and then weave into carbon fiber cloth, wherein the linear density of the roving is 2000tex, and the gram weight of the fiber cloth is 600g•m -2 ;
[0049] 2) Weigh 4g of graphene and 40g of expanded graphite and mix them by ball milling, wherein the ball milling speed is 2000r / min and the ball milling time is 4h; then place them in a 2wt% stannous nitrate solution, soak for a predetermined time, filter, soak the filtered solid in sodium hydroxide for 1h, filter, soak the filtered solid in hydrogen peroxide for 1h, filter, wash, and dry to obtain modified expanded graphite; disperse 80g of modified expanded graphite and 20g of phenolic resin in 250ml of N-methylpyrrolidone to obtain a mixed slurry;
[0050] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 180°C, a pressure of 20 MPa, and a hot pressing time of 30 min to obtain a plate blank;
[0051] 4) 150 g of epoxy acrylate, 200 g of methyl methacrylate, and 60 g of trimethylolpropane triacrylate were mixed evenly, and then 25 g of ceramic Ti3SiC2 nanopowder and 5 g of silane coupling agent were added thereto, and stirred evenly, and 5 g of benzoyl peroxide was added, and stirred evenly to obtain an impregnation solution;
[0052] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 30 minutes, then pressurize to 5Mpa, maintain for 30 minutes, repeat the evacuation and pressurization 5 times to make it fully impregnated;
[0053] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 80°C for 5 hours, and then placed in an oven for drying and curing at 150°C for 2 hours to obtain an ultra-thin graphite bipolar plate.
[0054] Comparative Example 1
[0055] 1) A plurality of carbon fibers are made into rovings and then woven into carbon fiber cloth, wherein the linear density of the rovings is 2000 tex and the weight of the fiber cloth is 600 g·m -2 ;
[0056] 2) Weighing 2g of graphene and 40g of expanded graphite and mixing them by ball milling, wherein the ball milling speed is 1800r / min and the ball milling time is 4h; then placing them in a 2wt% stannous nitrate solution, soaking them for a predetermined time, filtering, soaking the filtered solid in sodium hydroxide for 1h, filtering, soaking the filtered solid in hydrogen peroxide for 1h, filtering, washing, and drying to obtain modified expanded graphite; dispersing 75g of modified expanded graphite and 20g of phenolic resin in 200ml of N-methylpyrrolidone to obtain a mixed slurry;
[0057] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 160°C, a pressure of 20 MPa, and a hot pressing time of 30 min to obtain a plate blank;
[0058] 4) 120 g of epoxy acrylate, 200 g of methyl methacrylate, and 60 g of trimethylolpropane triacrylate were mixed evenly, and then 20 g of ceramic Ti3SiC2 nanopowder and 5 g of silane coupling agent were added thereto, and stirred evenly, and 5 g of benzoyl peroxide was added, and stirred evenly to obtain an impregnation solution;
[0059] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 20 minutes, then pressurize to 3Mpa, maintain for 20 minutes, repeat the evacuation and pressurization 5 times to make it fully impregnated;
[0060] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 80°C for 4 hours, and then placed in an oven for drying and curing at 150°C for 1 hour to obtain an ultra-thin graphite bipolar plate.
[0061] Comparative Example 2
[0062] 1) Disperse 18g of chloromethylated phenolic resin in 450ml of N,N-dimethylformamide, add 0.5g of sodium azide, react completely at 40°C, wash with water, and obtain azidophenolic resin; immerse 8g of carbon fiber in 4wt% hydrogen peroxide, heat at 80°C for 2h, take out and dry, then put into N-methylpyrrolidone containing 0.4wt% azidophenolic resin, heat at 150°C for 4h, take out and dry, and obtain pretreated carbon fiber; make a plurality of the pretreated carbon fibers into roving and then weave into carbon fiber cloth, wherein the linear density of the roving is 2000tex, and the gram weight of the fiber cloth is 600g•m -2 ;
[0063] 2) Dispersing 75 g of expanded graphite and 20 g of phenolic resin in 200 ml of N-methylpyrrolidone to obtain a mixed slurry;
[0064] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 160°C, a pressure of 20 MPa, and a hot pressing time of 30 min to obtain a plate blank;
[0065] 4) 120 g of epoxy acrylate, 200 g of methyl methacrylate, and 60 g of trimethylolpropane triacrylate were mixed evenly, and then 20 g of ceramic Ti3SiC2 nanopowder and 5 g of silane coupling agent were added thereto, and stirred evenly, and 5 g of benzoyl peroxide was added, and stirred evenly to obtain an impregnation solution;
[0066] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 20 minutes, then pressurize to 3Mpa, maintain for 20 minutes, repeat the evacuation and pressurization 5 times to make it fully impregnated;
[0067] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 80°C for 4 hours, and then placed in an oven for drying and curing at 150°C for 1 hour to obtain an ultra-thin graphite bipolar plate.
[0068] Comparative Example 3
[0069] 1) Disperse 18g of chloromethylated phenolic resin in 450ml of N,N-dimethylformamide, add 0.5g of sodium azide, react completely at 40°C, wash with water, and obtain azidophenolic resin; immerse 8g of carbon fiber in 4wt% hydrogen peroxide, heat at 80°C for 2h, take out and dry, then put into N-methylpyrrolidone containing 0.4wt% azidophenolic resin, heat at 150°C for 4h, take out and dry, and obtain pretreated carbon fiber; make a plurality of the pretreated carbon fibers into roving and then weave into carbon fiber cloth, wherein the linear density of the roving is 2000tex, and the gram weight of the fiber cloth is 600g•m -2 ;
[0070] 2) Weigh 2g of graphene and 40g of expanded graphite and mix them by ball milling, wherein the ball milling speed is 1800r / min and the ball milling time is 4h; then place them in a 2wt% stannous nitrate solution, soak for a predetermined time, filter, soak the filtered solid in sodium hydroxide for 1h, filter, soak the filtered solid in hydrogen peroxide for 1h, filter, wash, and dry to obtain modified expanded graphite; disperse 75g of modified expanded graphite, 20g of phenolic resin, 20g of ceramic Ti3SiC2 nanopowder and 5g of silane coupling agent in 200ml of N-methylpyrrolidone to obtain a mixed slurry;
[0071] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 160°C, a pressure of 20 MPa, and a hot pressing time of 30 min to obtain a plate blank;
[0072] 4) 120 g of epoxy acrylate, 200 g of methyl methacrylate and 60 g of trimethylolpropane triacrylate were mixed evenly, and then 5 g of benzoyl peroxide was added thereto, and stirred evenly to obtain an impregnation solution;
[0073] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 20 minutes, then pressurize to 3Mpa, maintain for 20 minutes, repeat the evacuation and pressurization 5 times to make it fully impregnated;
[0074] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 80°C for 4 hours, and then placed in an oven for drying and curing at 150°C for 1 hour to obtain an ultra-thin graphite bipolar plate.
[0075] Comparative Example 4
[0076] 1) Disperse 18g of chloromethylated phenolic resin in 450ml of N,N-dimethylformamide, add 0.5g of sodium azide, react completely at 40°C, wash with water, and obtain azidophenolic resin; immerse 8g of carbon fiber in 4wt% hydrogen peroxide, heat at 80°C for 2h, take out and dry, then put into N-methylpyrrolidone containing 0.4wt% azidophenolic resin, heat at 150°C for 4h, take out and dry, and obtain pretreated carbon fiber; make a plurality of the pretreated carbon fibers into roving and then weave into carbon fiber cloth, wherein the linear density of the roving is 2000tex, and the gram weight of the fiber cloth is 600g•m -2 ;
[0077] 2) Weighing 2g of graphene and 40g of expanded graphite and mixing them by ball milling, wherein the ball milling speed is 1800r / min and the ball milling time is 4h; then placing them in a 2wt% stannous nitrate solution, soaking them for a predetermined time, filtering, soaking the filtered solid in sodium hydroxide for 1h, filtering, soaking the filtered solid in hydrogen peroxide for 1h, filtering, washing, and drying to obtain modified expanded graphite; dispersing 75g of modified expanded graphite and 20g of phenolic resin in 200ml of N-methylpyrrolidone to obtain a mixed slurry;
[0078] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 160°C, a pressure of 20 MPa, and a hot pressing time of 30 min to obtain a plate blank;
[0079] 4) 120 g of epoxy acrylate and 260 g of methyl methacrylate were mixed evenly, and then 20 g of ceramic Ti3SiC2 nanopowder and 5 g of silane coupling agent were added thereto, and stirred evenly, and 5 g of benzoyl peroxide was added, and stirred evenly to obtain an impregnation solution;
[0080] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 20 minutes, then pressurize to 3Mpa, maintain for 20 minutes, repeat the evacuation and pressurization 5 times to make it fully impregnated;
[0081] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 80°C for 4 hours, and then placed in an oven for drying and curing at 150°C for 1 hour to obtain an ultra-thin graphite bipolar plate.
[0082] Comparative Example 5
[0083] 1) Disperse 18g of chloromethylated phenolic resin in 450ml of N,N-dimethylformamide, add 0.5g of sodium azide, react completely at 40°C, wash with water, and obtain azidophenolic resin; immerse 8g of carbon fiber in 4wt% hydrogen peroxide, heat at 80°C for 2h, take out and dry, then put into N-methylpyrrolidone containing 0.4wt% azidophenolic resin, heat at 150°C for 4h, take out and dry, and obtain pretreated carbon fiber; make a plurality of the pretreated carbon fibers into roving and then weave into carbon fiber cloth, wherein the linear density of the roving is 2000tex, and the gram weight of the fiber cloth is 600g•m -2 ;
[0084] 2) Weighing 2g of graphene and 40g of expanded graphite and mixing them by ball milling, wherein the ball milling speed is 1800r / min and the ball milling time is 4h; then placing them in a 2wt% stannous nitrate solution, soaking them for a predetermined time, filtering, soaking the filtered solid in sodium hydroxide for 1h, filtering, soaking the filtered solid in hydrogen peroxide for 1h, filtering, washing, and drying to obtain modified expanded graphite; dispersing 75g of modified expanded graphite and 20g of phenolic resin in 200ml of N-methylpyrrolidone to obtain a mixed slurry;
[0085] 3) The mixed slurry is evenly scraped onto the carbon fiber cloth, freeze-dried at -20°C, and then placed in a mold for hot pressing and curing at a temperature of 160°C, a pressure of 20 MPa, and a hot pressing time of 30 min to obtain a plate blank;
[0086] 4) 320 g of methyl methacrylate and 60 g of trimethylolpropane triacrylate were mixed evenly, and then 20 g of ceramic Ti3SiC2 nanopowder and 5 g of silane coupling agent were added thereto, and stirred evenly, and 5 g of benzoyl peroxide was added, and stirred evenly to obtain an impregnation solution;
[0087] 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, evacuate to 0.001Mpa, maintain for 20 minutes, then pressurize to 3Mpa, maintain for 20 minutes, repeat the evacuation and pressurization 5 times to make it fully impregnated;
[0088] 6) The impregnated expanded graphite sheet is heated and cured in a water bath at 80°C for 4 hours, and then placed in an oven for drying and curing at 150°C for 1 hour to obtain an ultra-thin graphite bipolar plate.
[0089] Experimental Section
[0090] The flexural strength of the graphite bipolar plate in Table 1 is tested with reference to the determination method for flexural strength of bipolar plate materials in GB / T 20042.1-2017; the electrical conductivity is calculated after testing with reference to the determination method for volume resistivity of bipolar plate materials in GB / T 20042.1-2017.
[0091] Table 1
[0092] Bending strength (Mpa) Conductivity (S / cm) Example 1 55.6 258 Example 2 56.2 262 Example 3 56.5 260 Example 4 56.1 265 Comparative Example 1 32.6 245 Comparative Example 2 48.6 210 Comparative Example 3 51.8 252 Comparative Example 4 49.6 235 Comparative Example 5 50.2 240
[0093] As can be seen from Table 1, the data in Comparative Example 1 show that the grafting treatment of carbon fiber can greatly affect the mechanical properties of the bipolar plate. As can be seen from the data in Comparative Example 2, the treatment of expanded graphite can significantly affect the conductive properties of the bipolar plate. As can be seen from Comparative Example 3, the addition method of ceramic Ti3SiC2 nanopowder can significantly affect the mechanical properties of the bipolar plate. As can be seen from Comparative Examples 4 and 5, the three-component mixture of epoxy acrylate, methyl methacrylate, and trimethylolpropane triacrylate can greatly affect the impregnation effect, thereby affecting the conductive properties of the bipolar plate. As can be seen from the data in the above embodiments and comparative examples, the grafted phenolic polyester It can improve the mechanical strength and bending performance of carbon fiber, and the bonding degree between the grafted material and the expanded graphite slurry is greatly improved, which improves the mechanical properties of the bipolar plate; graphene can greatly improve the conductivity of expanded graphite. At the same time, further surface modification with tin oxide improves the affinity with phenolic resin, so that graphene and expanded graphite can be evenly dispersed in the slurry to form a conductive network, improving the conductivity; titanium silicon carbide with high conductivity MAX phase is dispersed into the pores of the bipolar plate during the impregnation process, thereby improving the conductivity while avoiding the addition of MAX phase titanium silicon carbide to the plate, which leads to a decrease in the mechanical properties of the plate. After the three acrylate monomers are compounded, they have good wettability with the plate embryo, which is conducive to improving the conductivity.
[0094] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A method for manufacturing an ultra-thin graphite bipolar plate for a fuel cell, characterized in that: The following steps are involved: 1) dispersing chloromethylated phenolic resin in N,N-dimethylformamide, adding sodium azide, reacting, and obtaining azidophenolic resin; immersing carbon fiber in hydrogen peroxide, heating in a sealed state, taking out and drying, and then placing in N-methylpyrrolidone containing azidophenolic resin, heating in a sealed state, taking out and drying, and obtaining pretreated carbon fiber; making a plurality of the pretreated carbon fibers into roving and weaving them into carbon fiber cloth; 2) Weighing graphene and expanded graphite and mixing them by ball milling; then soaking them in a stannous nitrate solution, then soaking them in sodium hydroxide, and then soaking them in hydrogen peroxide to obtain expanded graphite modified with tin oxide and graphene; dispersing the modified expanded graphite and phenolic resin in N-methylpyrrolidone to obtain a mixed slurry; 3) The mixed slurry is evenly coated on the carbon fiber cloth, freeze-dried, and then hot-pressed to obtain a plate blank; 4) epoxy acrylate, methyl methacrylate and trimethylolpropane triacrylate are mixed evenly, and then ceramic Ti3SiC2 nano powder and silane coupling agent are added thereto, stirred evenly, and a peroxide initiator is added to obtain an impregnation solution; 5) Transfer the plate to a sealed container, inject the impregnation liquid, immerse the plate embryo in the impregnation liquid, and repeat vacuuming and pressurizing to make it fully impregnated; 6) The impregnated expanded graphite sheet is heated and cured in a water bath, and then placed in an oven for drying and curing to obtain an ultra-thin graphite bipolar plate.
2. The method for manufacturing an ultra-thin graphite bipolar plate according to claim 1, wherein in step 1, 18-20 g of chloromethylated phenolic resin is dispersed in 450-500 ml of N,N-dimethylformamide, 0.5-0.6 g of sodium azide is added, the reaction is completed at 40-50 ° C, and the mixture is washed with water to obtain an azidized phenolic resin; 8-10 g of carbon fiber is immersed in hydrogen peroxide with a concentration of 4-6 wt%, heated in a sealed state at 80-100 ° C for 1-2 h, taken out and dried, and then placed in N-methylpyrrolidone containing 0.4-0.5 wt% of azidized phenolic resin, heated in a sealed state at 150-180 ° C for 2-4 h, taken out and dried to obtain pretreated carbon fiber.
3. The method for manufacturing an ultrathin graphite bipolar plate according to claim 1, wherein in step 2, 2-4 g of graphene and 40-50 g of expanded graphite are weighed and mixed by ball milling; then placed in a stannous nitrate solution having a concentration of 2-3 wt%, soaked for a predetermined time, filtered, the solid obtained by filtration is placed in sodium hydroxide and soaked for 0.5-1 h, filtered, the solid obtained by filtration is placed in hydrogen peroxide and soaked for 0.5-1 h, filtered, washed, and dried to obtain modified expanded graphite; 75-80 g of modified expanded graphite and 20-25 g of phenolic resin are dispersed in 200-250 ml of N-methylpyrrolidone to obtain a mixed slurry.
4. The method for manufacturing an ultra-thin graphite bipolar plate according to claim 1, wherein the parameters of the hot pressing curing in step 3 are as follows: a hot pressing temperature of 160-180° C., a pressure of 15-25 MPa, and a hot pressing time of 10-30 min; and a polar plate blank is obtained.
5. The method for manufacturing an ultra-thin graphite bipolar plate according to claim 1, wherein in step 4, 120-150 g of epoxy acrylate, 200-220 g of methyl methacrylate, and 60-80 g of trimethylolpropane triacrylate are mixed uniformly, and then 20-25 g of ceramic Ti3SiC2 nanopowder and 5-10 g of silane coupling agent are added thereto, stirred uniformly, and 5-10 g of benzoyl peroxide is added, and stirred uniformly to obtain an impregnation solution.
6. The method for manufacturing an ultra-thin graphite bipolar plate according to claim 1, wherein in step 5, the electrode plate is transferred to a closed container, an impregnation liquid is injected, the electrode plate blank is immersed in the impregnation liquid, the vacuum is evacuated to below 100 Pa, maintained for 20-30 minutes, and then pressurized to 3-5 MPa, maintained for 20-30 minutes, and the vacuum and pressurization are repeated 3-5 times to fully impregnate it.
7. The method for manufacturing an ultra-thin graphite bipolar plate according to claim 1, wherein in step 6, the temperature of the water bath is 80-90°C for 4-5 hours, and then the plate is placed in an oven for drying and curing at a temperature of 150-170°C for 1-2 hours to obtain an ultra-thin graphite bipolar plate.
8. An ultra-thin graphite bipolar plate for a fuel cell, characterized in that: The electrode plate is prepared by the manufacturing method according to any one of claims 1 to 7.
